Corrupção no âmbito municipal: o caso Sevandija em Ribeirão Preto - Almeida, Tailon Rodrigues (Universidade Federal de São Carlos, 2020)
This research addresses the phenomenon of political corruption at the municipal level, and its scope of work consists in conducting a case study having as its object of analysis the corruption scandal entitled Sevandija, which occurred in Ribeirão Preto, in the State of São Paulo, Brazil, during the second administration of former Mayor Dárcy Vera (PSD), between 2013 and 2016. We maintain that the institutions have strong relevance in the study of the proposed theme and we seek to combine the theoretical debate about Local Power with the institutional study of corruption. The general objective that guides our research is to analyze the institutional conditions of the municipal administration that allowed the practice of corruption. In this sense, we fundamentally seek to answer the following question: What are the institutional conditions that made possible the practice of corruption in Ribeirão Preto? The specific objectives of this research are: (1) to map the institutional circuits where the illicit practices occurred in Ribeirão Preto and; (2) to analyze the institutional mechanisms that made it possible to halt the actions of the assembled CPIs to investigate signs of irregularities in the municipality's budget execution. We use a qualitative methodology based on the case study focusing on historical neoinstitutionalism combined with semi-structured interviews with prosecutor Leonardo Leonel Romanelli, who coordinated the investigations by GAECO, and councilor Marcos André Papa (REDE), who chaired the CPI of Daerp. From the listed methodology, and in order to achieve the proposed objectives and answer the research question, we will analyze the following material: semi-structured interviews; minutes of legislative sessions at which CPIs were voted; investigation reports and case files prepared by the Public Prosecution Service in conjunction with GAECO; Internal Regulations of the Ribeirão Preto City Council; the Organic Law of the Municipality.
Corruption at the municipal level: the Sevandija case in Ribeirão Preto
Keywords: Corrupção; Poder local; Instituições políticas; Ribeirão Preto; Corruption; Local-power; Politics Institutions; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO; CIENCIAS HUMANAS::CIENCIA POLITICA